“No more a child, not yet an adult”: studying social cognition in adolescence - Brizio, Adelina; Gabbatore, Ilaria; Tirassa, Maurizio; Bosco, Francesca M. (Frontiers in Psychology, 2015)
There are several reasons why adolescence is interesting. It is in this phase that an individual finds herself fully facing the external world: basically equipped with the kind of social cognition that s/he has acquired at home, at school and through the media during childhood, s/he has now to meet a host of other, diverse views of what "reasonable", "appropriate" or "expected" courses of thought and emotions are, in the wild with friends and peers, romantic or sexual partners, teachers and employers, and the society at large. Furthermore, she is also expected, both at home and in the external world, to have a wholly new degree of control over such courses. While the idea that the development of social cognition still progresses after infancy (and possibly throughout the life span) is clearly gaining consensus in the field, the literature building on it is still scarce. One of the reasons for this probably is that most tests used to study it focus on its basic component, namely ToM, and have been mostly devised for us with children; therefore, they are not suitable to deal with the hugely increasing complexity of social and mental life during adolescence and adulthood. Starting from a review of the literatuer available, we will argue that the development of social cognition should be viewed as a largely yet-to-be-understood mix of biological and cultural factors. While it is widely agreed upon that the very initial manifestations of social life in the newborn are largely driven by an innate engine with which all humans are equally endowed, it is also evident that each culture, and each individual within it, develops specific adult versions of social cognition.